Experimental study on the effect of reflow soldering temperature profile on the solder joint shape - Bo Wang; Xuexia Yang; Yu Zhang; Xuefeng Shu (2010 11th International Conference on Electronic Packaging Technology and High Density Packaging, 2010)
In this paper, Surface mount experiment of Sn-Pb and Lead-Free solder joints under different thermal reflow profile was aimed at statistical analysis of the reflowed cross-section contour and shape parameters (height, diameter and contact angle). The results as follows: Reflowed solder joints was a pot-shaped body which the top pad is slightly smaller than the bottom pad, and the maximum diameter of solder joints in the side was under the central position; Solder joint shapes obtained from different thermal reflow profiles have greatly differences; The smaller heating factors, the higher height and the smaller diameter and contact angle of solder joint formed by welding.